Functional and Dysfunctional Neuroplasticity in Learning to Cope with Stress - Simona Cabib; Paolo Campus; David Conversi; Cristina Orsini; Stefano Puglisi-Allegra (Brain Sciences, 2020)
In this brief review, we present evidence of the primary role of learning-associated plasticity in the development of either adaptive or maladaptive coping strategies. Successful interactions with novel stressors foster plasticity within the neural circuits supporting acquisition, consolidation, retrieval, and extinction of instrumental learning leading to development of a rich repertoire of flexible and context-specific adaptive coping responses, whereas prolonged or repeated exposure to inescapable/uncontrollable stressors fosters dysfunctional plasticity within the learning circuits leading to perseverant and inflexible maladaptive coping strategies. Finally, the results collected using an animal model of genotype-specific coping styles indicate the engagement of different molecular networks and the opposite direction of stress effects (reduced vs. enhanced gene expression) in stressed animals, as well as different behavioral alterations, in line with differences in the symptoms profile associated with post-traumatic stress disorder.